2016
DOI: 10.1093/humrep/dew173
|View full text |Cite
|
Sign up to set email alerts
|

No change in live birthweight of IVF singleton deliveries over an 18-year period despite significant clinical and laboratory changes

Abstract: Not applicable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 54 publications
3
16
1
Order By: Relevance
“…Our findings are in line with several earlier reports in which a higher birth weight and higher risk of LGA and macrosomia are described in children born after FET compared with fresh embryo transfer and NC (Feng et al, 2012;Henningsen et al, 2011;Kato et al, 2012;Maas et al, 2016;Nakashima et al, 2013;Ozgur et al, 2015;Pelkonen et al, 2010;Pinborg et al, 2014;Roy et al, 2014;Shih et al, 2008). Our findings are also consistent with previous systematic reviews on perinatal outcome following FET (Maheshwari, Pandey, Shetty, Hamilton, & Bhattacharya, 2012;Maheshwari et al, 2016).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our findings are in line with several earlier reports in which a higher birth weight and higher risk of LGA and macrosomia are described in children born after FET compared with fresh embryo transfer and NC (Feng et al, 2012;Henningsen et al, 2011;Kato et al, 2012;Maas et al, 2016;Nakashima et al, 2013;Ozgur et al, 2015;Pelkonen et al, 2010;Pinborg et al, 2014;Roy et al, 2014;Shih et al, 2008). Our findings are also consistent with previous systematic reviews on perinatal outcome following FET (Maheshwari, Pandey, Shetty, Hamilton, & Bhattacharya, 2012;Maheshwari et al, 2016).…”
Section: Discussionsupporting
confidence: 93%
“…A few studies have reported adjusted risk ratio (ARR) instead of AOR in their studies (Litzky et al, 2017;Maas et al, 2016;Maheshwari, Raja, & Bhattacharya, 2016) (Table 2).…”
Section: Statisticsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent research, it was shown that BMI is an independent risk factor for being LGA; however, the investigators were unable to show a connection between BMI and transfer of cryopreserved embryos and therefore conclude that FET is also an independent risk factor for being LGA [48]. Other possible explanations could be the ART procedures itself, embryo quality or maternal factors [11,49,50]. We aim to prolong our study to assess the influence of embryo quality, ART procedures and lifestyle factors.…”
Section: Discussionmentioning
confidence: 94%
“…Additionally, as more data emerge regarding the improved perinatal outcomes with FET cycles as compared to fresh embryo transfer cycles, including less preterm delivery and fewer small-for-gestational age neonates, there are fewer reasons to proceed with a fresh embryo transfer if cryopreservation is an option. 3942 …”
Section: Frozen Embryo Transfersmentioning
confidence: 99%